The Effect of Investment, Economic Growth and Education Level on Employment Opportunities and Poverty by Province in Indonesia - Wiriana, I Gede; Sudibia, I Ketut (Jurnal Ekonomi Kuantitatif Terapan, 2022)
The aims of this study are (1) to analyze the effect of investment, economic growth and education level on employment opportunities by province in Indonesia, (2) to analyze the effect of investment, economic growth, education level and employment opportunity on poverty by province in Indonesia, (3 ) to analyze the indirect effect of investment, economic growth and education level on poverty through employment opportunities by province in Indonesia. The research method uses a quantitative research design with an associative expansion level. This study uses secondary data from the Central Statistics Agency, with a total of 170 observations. The data analysis techniques used are descriptive techniques and path analysis with the application of multiple linear regression models with the help of the SPSS program. The results showed that (1) investment, economic growth and education level had a positive and significant effect on employment opportunities, (2) investment had a negative and significant effect on poverty, (3) economic growth, education level and employment opportunities did not negatively affect poverty, (4) employment opportunities as an intervening variable indirect effect between investment, economic growth and education level on poverty.